Komunikasi Informasi Edukasi Anti Pinjaman Online Ilegal bagi Ibu Rumah Tangga di PKBM An-Nadhif - Rangga Galura Gumelar; Ikhsan Ahmad; Iman Mukhroman (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Illegal online lending has become a serious threat to low-income families, particularly housewives who are vulnerable to predatory lending practices and debt collector intimidation. This community service activity aims to improve the understanding of housewives at PKBM An-Nadhif, Serang Regency, regarding the dangers of illegal online lending and healthy financial alternatives through a Communication, Information, and Education (CIE) approach. The implementation method covers three stages, preparation, implementation, and evaluation, using pre-tests and post-tests administered to 35 participants. Activities were conducted through interactive lectures, group discussions, case simulations, and the promotion of formal financial services. Evaluation results indicated an improvement in understanding of illegal online lending characteristics by 72.4%, legal and social risks by 65.8%, and formal financial alternatives by 58.3%. The average participant score increased from 46.2 to 76.8, representing a 66.2% improvement (p < 0.001). The CIE approach proved effective in enhancing financial literacy and the community's critical awareness of illegal online lending.